Sugammadex Versus Neostigmine for Reversal of Rocuronium Neuromuscular Block in Patients Having Catheter-Based Neurointerventional Procedures: A Randomized Trial. (11th May 2021) - Farag, Ehab; Rivas, Eva; Bravo, Mauro; Hussain, Shazam; Argalious, Maged; Khanna, Sandeep; Seif, John; Pu, Xuan; Mao, Guangmei; Bain, Mark; Elgabaly, Mohamed; Esa, Wael Ali Sakr; et al.
Abstract : BACKGROUND: Catheter-based endovascular neurointerventions require deep neuromuscular blocks during the procedure and rapid subsequent recovery of strength to facilitate neurological evaluation. We tested the primary hypothesis that sugammadex reverses deep neuromuscular blocks faster than neostigmine reverses moderate neuromuscular blocks. METHODS: Patients having catheter-based cerebral neurointerventional procedures were randomized to: (1) deep rocuronium neuromuscular block with posttetanic count 1 to 2 and 4-mg/kg sugammadex as the reversal agent or (2) moderate rocuronium neuromuscular block with train-of-four (TOF) count 1 during the procedure and neuromuscular reversal with 0.07-mg/kg neostigmine to a maximum of 5 mg. Recovery of diaphragmatic function was assessed by ultrasound at baseline before the procedure and 90 minutes thereafter. The primary outcome—time to reach a TOF ratio ≥0.9 after administration of the designated reversal agent—was analyzed with a log-rank test. Secondary outcomes included time to successful tracheal extubation and the difference between postoperative and preoperative diaphragmatic contraction speed and distance. RESULTS: Thirty-five patients were randomized to sugammadex and 33 to neostigmine. Baseline characteristics and surgical factors were well balanced. The median time to reach TOF ratio ≥0.9 was 3 minutes (95% confidence interval [CI], 2-3 minutes) in patients given sugammadex versus 8 minutes (95% CI, 6-10 minutes) in patients given neostigmine. Sugammadex was significantly faster by a median of 5 minutes (95% CI, 3-6 minutes; P < .001). However, times to tracheal extubation and diaphragmatic function at 90 minutes did not differ significantly. CONCLUSIONS: Sugammadex reversed deep rocuronium neuromuscular blocks considerably faster than neostigmine reversed moderate neuromuscular blocks. However, times to extubation did not differ significantly, apparently because extubation was largely determined by the time required for awaking from general anesthesia and because clinicians were willing to extubate before full neuromuscular recovery. Sugammadex may nonetheless be preferable to procedures that require a deep neuromuscular block and rapid recovery.